Pengaruh Lokasi, Harga, Keragaman Menu Terhadap Keputusan Pembelian (Study Kasus Pelaggan Kedai Pesenkopi Dinoyo Di Kelurahan Dinoyo) - Aulia Rakhma Sari; N. Rachma; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This research was conducted at the Dinoyo Pesenkopi Kedai in Dinoyo Village. The type of research used is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of location, price and menu diversity on purchasing decisions. The independent variables used are location, price and menu variety, while the dependent variable is purchasing decisions. The sample used in this study were 100 respondents who were customers of Kedai Pesenkopi Dinoyo in Dinoyo Village. Data collection techniques using a questionnaire. The analytical method used is the instrument test, multiple linear regression analysis, classical assumption test, determination test, f test and t test using SPSS 16.0 computer software for data processing. The results of this study indicate that location affects purchasing decisions, price affects purchasing decisions and menu diversity affects purchasing decisions. location, price and variety of menus simultaneously affect purchasing decisions. Keywords: Location, Price and Menu Diversity and Purchase Decision.